Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Jasa Transportasi Bus Pariwisata PT. Midas Transportasi Bogor - Nabilla Aulia (Politeknik Kampar, 2023)
The tight competition among companies engaged in tourism bus transportation services encourages companies to look for the right marketing strategy so that the company can win the competition, one strategy to win the competition is to provide customer satisfaction. Factors that influence customer satisfaction include service quality and price. This study aims to analyze the effect of service quality and price on consumer satisfaction of PT. Midas Transportation Bogor. Based on the results of this research is expected to be useful as input and information for the PT. Midas Transportation Bogor regarding the factors that influence customer satisfaction such as service quality, and price in order to be able to meet the criteria of customer satisfaction. The population of this study are consumers who have used the tourism bus transportation services of PT. Midas Transportation Bogor. The sample in this study were 64 consumers of tourism bus transportation services of PT. Midas Transportation Bogor. Testing the coefficient of determination (R2) is 51.4% while the rest is 48.6%. The relationship between service quality and price is strong with a correlation coefficient of 0.717. Based on the results of hypothesis testing, it shows that the variables of service quality and price simultaneously or partially have a positive and significant effect on consumer satisfaction of tourism bus transportation services at PT. Midas Transportation Bogor.